CO2-switchable emulsions with controllable size and viscosity. Issue 12 (7th March 2023) - Jiang, Jianzhong; Li, Huaixin; Gu, Yao
Abstract : CO2 -switchable emulsions with on-demand stability and controllable properties, such as droplet size, viscosity, and emulsion type, were prepared with a CO2 -switchable surfactant and silica nanoparticles. Abstract : CO2 -responsive emulsions have attracted considerable attention in recent years because of their biocompatibility and easy removal of CO2 . However, most CO2 -responsive emulsions are only used in stabilization and demulsification processes. In this paper, we report CO2 -switchable oil-in-dispersion (OID) emulsions co-stabilized with silica nanoparticles and anionic NCOONa, in which the required concentrations of NCOONa and silica particles were as low as 0.01 mM and 0.0001 wt%, respectively. Besides reversible emulsification/demulsification, the aqueous phase containing the emulsifiers was recycled and reused with the CO2 /N2 trigger. More importantly, the properties of the emulsions, such as droplet sizes (40–1020 μm) and viscosities (6–2190 Pa s), were intelligently controlled by the CO2 /N2 trigger, and meanwhile reversible conversion between OID emulsions and Pickering emulsions was achieved. The present method offers a green and sustainable way to regulate the emulsion states, which enables smart control of emulsions and widens their potential applications.